Utilizing wastewater as nutrition source for the cultivation of Chlorella vulgaris - Roshdy, Ali Mohamed (AUC Knowledge Fountain, 2019)
Investigating alternatives for fossil fuels have always been an area of interest for scientist around the globe. The decline in the oil & gas stock along with the increasing demand for energy that accompanies the increase in population has created the need for an alternative energy solution. From the renewable energy solution, microalgae stand out as a very promising source for biofuel production due to its high lipid content. However, the production of biofuel from microalgae is still of a high cost compared to production of the same amount from fossil fuels. The unfeasibility commercial production for biofuel from microalgae goes back to the high cost in the cultivation process, mainly supply the cultivation medium with nutrients, extraction process, and transesterification process. This research aimed to reduce the cultivation process cost by investigating the substitution of required nutrients in the synthetic Woods Hole MBL (MBL) medium by those available in wastewater streams. Chlorella vulgaris was selected for this research for its high biomass productivity and its ability for adaptation in various media. Different cultivation conditions were tested to reach to growth rate close to which was recorded from the cultivation on synthetic medium (MBL). The research reached to the conclusion that a mixture between synthetic medium (MBL) and non-sterilized agriculture wastewater under indirect sunlight (16:8 light to dark cycle) achieved a growth rate close to the growth rate from cultivation on a pure synthetic medium (MBL). Regarding total lipids, The non-sterilizer agriculture wastewater and MBL mixture achieved the highest results after fourteen cultivation days. Both growth rates and total lipid results prove that a mixture between agriculture wastewater and synthetic medium (MBL) can be utilized as a substitution for the pure MBL medium. This substitution will support the objective of reducing the total cost for producing biofuel from microalgae.